Analysing the impact of cultural diversity on stakeholder engagement in multinational construction projects - Ndlovu, Siphamandla Benedict (Department of Construction Economics and Management, 2025)
A significant challenge faced by project managers in multinational construction projects is effectively managing stakeholders from various national cultures. Effective engagement of stakeholders from diverse cultural backgrounds significantly enhances the likelihood of success in project management and project. This study utilizes a systematic method to qualitative approach, employing three empirical case studies to reveal the elements that influence stakeholder engagement in multinational projects. The main research questions are: What are the impacts of national culture in the engagement of project stakeholders in international construction projects, and how can project managers utilize and improve standard stakeholder engagement tools and procedures in managing multinational stakeholders? Section 1 included a concise overview of the problem and established the precise meanings of important terminology by outlining the introduction of the research. Section 2 outlined the literature review of the subject and research area. The author provide a comprehensive explanation of the methodology employed for the study in Section 3, while Section 4 presents and analyse the data collected from empirical study and the elements that were identified as being associated with the literature review. Building upon the previous part's, section 5 offers insights into prospective future avenues of research for managing multi national projects and offers recommendations on the subject. The study's findings suggest a significant inverse relationship between stakeholder engagement methods and cultural disparities in multinational construction projects. Especially in the areas of bias, work performance, communication, behaviour, decision-making, and conflict management. The study further discovered that effective communication, cultural awareness, challenging stereotypes, and early stakeholders' identification might enhance stakeholder engagement methods.